Galinsoga parviflora restored associated motor coordination through increased linear distribution of Purkinje Cells in mercury chloride-induced toxicity of mice’s cerebellum - Ayuba, John Tabakwot; Ayodeji Okesina, Akeem; Ibe, Michael Usman; Kunle Ajenikoko, Michael; Theophilus, Pius; Kusiima, Nicholas; Odoma, Saidi; Edgar, Mario Fernandez (African Journal of Cellular Pathology, 2022)
Mercury (Hg) is a poisonous substance associated with diseases, such as ataxia and Joubert syndrome. Therefore, it is important to find a way to disrupt the process of Hg poisoning in the cerebellum, by exploring the medicinal value of local herb such as Galinsoga parviflora (GP). This study examined the effects of aqueous leaf extract of GP in HgCl2-induced cerebellar toxicity in adult male mice. Twenty-five adult male mice of an average weight of 25 g were randomly divided into 5 groups (n=5). Animals in Group I received oral administration of 2 ml/kg distilled water for 6 weeks, Group II received 2.3 mg/kg of HgCl2 for 3 weeks, Group III received 2.3 mg/kg of HgCl2 for the first 3 weeks followed by oral administration of 800mg/kg of GP extract for the next 3 weeks, Group IV received 800mg/kg of GP extract for the first 3 weeks followed by 2.3 mg/kg of HgCl2 for the next three weeks, and Group V received 2.3 mg/kg of HgCl2 and 800 mg/kg of GP extract concurrently for three weeks. The test animals were subjected to beam walking tests during the experiment period, followed by euthanasia, perfusion fixation, and tissue sample collection for histological and histochemical analysis. Treatment with the extract of GP showed varying degrees of regeneration in the cerebellar Purkinje cells and myelin sheath of mice in HgCl2 induced toxicity, with corresponding improvements in balance and posture. Cerebellar HgCl2 exposure in the present study was neurotoxic; however, treatment with GP was of therapeutic value.
Keywords: Mercury chloride; Cerebellum; Galinsoga parviflora